Design and validation of the Scale of Attitudes Toward Persons with Disabilities (SAPD) in Peruvian citizens - Ruiz Fasabi, Edinson Moises (2025)
The objective of the research was to design and validate a scale of attitudes toward people with disabilities (SAPD) among Peruvian citizens. The design was instrumental and psychometric in nature. The sample consisted of 658 participants from a province in San Martín between the ages of 18 and 75 (M = 32.4; SD = 11.7), 54.3% of whom were women and 45.7% men. The results were validated using Aiken's V by five experts V = .93. Reliability was obtained using Cronbach's alpha coefficient (a = 0.924) and McDonald's omega (w = 0.930). Likewise, the Kaiser Meyer Olkin (KMO) sample adequacy test reached a value of 0.879 and an explained variance of 67.683%, grouping the items into 3 dimensions and 3 categories, while the AFC showed adequate adjustment indices. In conclusion, the Scale of Attitudes toward People with Disabilities has adequate psychometric properties and is a valid and reliable instrument for application within the established population. In this sense, the study lays the foundation for future research and actions aimed at promoting a culture of respect and equity for people with disabilities.